For whom the bell tolls - Hemingway, Ernest, 1899-1961. (New York : Scribner, 1968)
The story of an American, Robert Jordan, who fought during the Civil War in Spain with the anti-fascist guerrillas in the mountains.
First published in 1940.
Keywords: Spain -- History -- CIvil War, 1936-1939 -- Fiction